Bowel preparation in pediatric colonoscopy: results of an open observational study - Berger, Thomas; Classen, Martin; Engelhardt, Harald; Keller, Klaus-Michael; Laass, Martin W.; Melchior, Ralph; Posovszky, Carsten; Rodeck, Burkhard; Schaper, Katharina; Behrens, Rolf (Endoscopy International Open, 2016)
Background and study aims: The goal of this study was to analyze the bowel cleansing methods currently used for pediatric colonoscopy in terms of effectiveness, tolerance and safety.Patients and methods: Data from 768 colonoscopies reported by 28 centers were registered in an online database for further analysis. Binary logistic regression was used to determine how preparation methods affected the cleaning effect (Aronchick score) and the rate of adverse events (Aes) and complications.Results: The most frequently reported cleansing agents were sodium picosulphate (54.2 %) and polyethylene-glycol (41.3 %) in various combinations. The cleaning effect was good to excellent in 72.6 % of patients. AEs during the preparation period occurred in 21.5 % of patients. Complications during endoscopy were reported in 12.1 % and were mostly mild. The different agents had no influence on the cleaning effect. In contrast the risk of AEs during preparation was significantly increased when polyethylene-glycol was used (odds ratio (OR) 2.112, P = 0.002) but reduced with the use of sodium picosulphate (OR 0.380, P < 0.001). In particular, the risk of needing a nasogastric tube to complete clean-out was about 10-fold higher when polyethylene-glycol was used.Conclusions: A large variety of regimens are used for bowel preparation in children. We found a good overall cleaning result independent of the agents used. Cleansing agents, on the other hand, had a significant influence on tolerance and safety.